THE ROLE OF SMALL AND MEDIUM ENTERPRISES IN FOREIGN INVESTMENT AND EXTERNAL TRADE THE CASE OF ALGERIA DURING THE PERIOD 2000-2018 - Belhadi, Soufiane; Eddine, Ikhlef Djamel (The journal of contemporary issues in business and government, 2022)
The topic of medium and small-sized enterprises presents itself for study due to the ambiguity surrounding it at several levels, in terms of its definition and characteristics, as it is the engine supporting the economies of many developed countries due to the special interests given to them by the latter. Algeria is a distinguished place, and this is what reality reflects in terms of laying out several programs to support and promote it, and in return, and what is the role that these institutions played in attracting foreign investments and promoting external trade. We note that small and medium enterprises do not represent a great temptation for the foreign investor due to their small size in exchange for their low profitability, and we do not forget the investment climate surrounding them, while we find that they have a distinct role in exports outside of hydrocarbons.